THE GEOGRAPHICAL LEGACY OF IBN HAWQAL: CONTINUITY OF THE ARAB CARTOGRAPHIC (BALKHI) SCHOOL AND THE HISTORICAL-GEOGRAPHICAL IMAGE OF THE VOLGA-CASPIAN REGION (Journal of Oriental Studies, 2026)
History and geography, as fundamental concepts for studying and interpreting time and space, have played a crucial role in shaping the foundation of human civilization. One of the cultural and scientific legacies that emerged at the intersection of these two philosophical concepts is the field of historical maps. Historical maps are not only valuable sources of information about past events and phenomena but also prominent tools that reflect the spatial perception and worldview paradigm of medieval Muslim society. Through such maps, researchers can analyze in depth the geographical understanding, political structures, and intercultural connections of historical periods. This article examines the formation of the “Balkhi School,” considered the golden foundation of medieval Islamic cartography, and the geographical legacy of its prominent representative, Ibn Hawqal. The primary focus of the study is to identify the scientific tradition of the school founded by Abu Zayd al-Balkhi and its continuity in the works of Ibn Hawqal and Abu Ishaq al-Istakhri. Given the scope and objectives of the article, a historical-genetic method was employed. This approach allowed for the study of the origins and evolutionary development of Arab cartography. In addition, through comparative analysis and source-based examination, textual data and cartographic images from foundational works such as Kitab al-Masalik wa al-Mamalik and Surat al-Aqalim were compared. The interdisciplinary approach enabled a careful consideration of this issue at the intersection of geography, history, cultural studies, and philosophy, allowing the map to be interpreted not only as a geographical tool but also as a cultural-cognitive phenomenon. Furthermore, the article comparatively analyzed the works of international scholars, orientalists, and historians alongside Arab geographers.Keywords: Ibn Hawqal, Balkhi School, Islamic cartography, al-Istakhri, Kitab al-Masalik wa al-Mamalik, ethnography of the Volga–Caspian peoples, Surat al-Aqalim.